Implementasi Model Pembelajaran Berdiferensiasi Dalam Kurikulum Merdeka di Sekolah Dasar Bakateu Kabupaten Malaka Nusa Tenggara Timur - Yanuarius Bria Seran; Damian Puling (LPPM Politeknik Pratama, 2023)
The teacher's ability to accommodate the diversity of characteristics and interests of students is the key to the success of the learning process itself. The Differentiated Learning Model is an adaptation effort in the classroom to meet students' learning needs. Therefore, we want to study further how differentiated learning is implemented in social studies learning, as well as the impact of differentiated learning in social studies learning for class V students at SDN Bakateu, Malaka Regency, East Nusa Tenggara. This research is qualitative with a descriptive approach. Research data collection was obtained through interviews, observation and documentation. So the research instruments used consisted of interview guide sheets, observation guides, and documentation. The data obtained was analyzed using data analysis techniques consisting of Data reduction, Data Display, and conclusion drawing/Verification. Based on the results of data analysis, it can be concluded that there are several stages that must be fulfilled in differentiated social studies learning, namely mapping students' needs through diagnostic assessments, designing differentiated learning plans according to students' needs, and evaluating and reflecting on learning that has taken place. The implementation of differentiated social studies learning has a positive impact on students as shown by the increased enthusiasm and enthusiasm of students during learning.